Relay in the loop test procedures for adaptive overcurrent protection - Piesciorovsky, Emilio C. (Kansas State University, 2015)
Microgrids with distributed generators have changed how protection and control systems are designed. Protection systems in conventional U.S. distribution systems are radial with the assumption that current flows always from the utility source to the end user. However, in a microgrid with distributed generators, currents along power lines do not always flow in one direction. Therefore, protection systems must be adapted to different circuit paths depending on distributed generator sites in the microgrid and maximum fuse ampere ratings on busses. Adaptive overcurrent protection focuses on objectives and constraints based on operation, maximum load demand, equipment, and utility service limitations. Adaptive overcurrent protection was designed to protect the power lines and bus feeders of the microgrid with distributed generators by coordinating fuses and relays in the microgrid. Adaptive overcurrent protection was based on the relay setting group and protection logic methods. Non-real-time simulator (NRTS) and real-time simulator (RTS) experiments were performed with computer-based simulators. Tests with two relays in the loop proved that primary relays tripped faster than backup relays for selectivity coordination in the adaptive overcurrent protection system. Relay test results from tripping and non-tripping tests showed that adaptive inverse time overcurrent protection achieved selectivity, speed, and reliability. The RTS and NRTS with two relays in the loop techniques were described and compared in this work. The author was the first graduate student to implement real-time simulation with two relays in the loop at the Burns & McDonnell - K-State Smart Grid Laboratory. The RTS experimental circuit and project are detailed in this work so other graduate students can apply this technique with relays in the loop in smart grid research areas such as phasor measurement units, adaptive protection, communication, and cyber security applications.
Keywords: Adaptive protection; Relay test systems; Real-time simulator with relays-in-the-loop; Power system protection; Microgrid with distributed generators; Smart grid lab; Electrical Engineering (0544)